Strategic study on energy-protein requirements for local sheep : 1 . Growing phase - I-Wayan Mathius; M Martawidjaja; A Wilson; T Manurung (Indonesian Center for Animal Research and Development (ICARD), 1996)
Fourty, thin-tail lambs (mean BW 13 .8 ± 1 .1 kg) were used in an experiment to measure energy and protein requirements. Lambs were divided into four dietary treatments in a 2 x 2 x 2 factorial design in which the factors were sex (male vs female), energy levels (high vs low) and crude protein (high vs low) . Metabol izable energy (ME) and crude protein (CP) requirements were measured by regression technique, using data collected during the experiment . Results showed that combination of low protein and high energy diet gave the highest response, i.e . 112 g daily gain with better feed convertion, i .e . 5 .4 . Equation models developed to predict ME and CP requirements were EM (MJ/head) = -11 .9266 - 0 .6487 BW °.